Improving rock ramp fishways for small-bodied Great Plains fishes - Swarr, Tyler R., author; Myrick, Christopher A., advisor; Bestgen, Kevin R., committee member; Bledsoe, Brian P., committee member (Colorado State University. Libraries, 2018)
The growing global need to improve the longitudinal connectivity of lotic systems is often met by using fish passage structures (fishways). When designing fishways in the past, biologists and engineers focused primarily on strong swimming species such as salmonids. However, the majority of riverine species in the interior United States are not salmonids and may be excluded by fishways built using salmonid criteria due to lower swimming abilities and/or behavioral differences. I designed and built a 9.1-m long adjustable hydraulic research flume at the Colorado State University Foothills Fisheries Laboratory (FFL) to test fish passage and evaluate the effects of grade (slopes of 2 – 10%, in 2% increments) on the passage success of three Great Plains fish species: Flathead Chub Platygobio gracilis, Stonecat Noturus flavus, and Arkansas Darter Etheostoma cragini. A 6.1-m long rock ramp fishway was installed in the flume and four PIT tag antennas were used to detect full or partial passage success. In order to test the key assumption that tagging does not affect fish performance, I evaluated the impacts of 8-mm PIT tags on Arkansas Darter and found no significant difference in the survival and swimming abilities of PIT tagged fish versus non-tagged fish. A review of the literature on small-bodied fish PIT tagging suggests that suturing incisions of surgically implanted PIT tags of small-bodied fishes should be avoided to reduce mortality. Prior studies had already demonstrated that Stonecats and Flathead Chub could be tagged without incurring performance losses. I used the Cormack-Jolly-Seber (CJS) model in Program MARK to determine the probability of full and partial passage success over the fishway based on the PIT tag detection history of each fish at each antenna. Passage success to upstream antennas was highest at shorter distances and at lower slopes for all species. Probability of passage success was highest for Flathead Chub, followed by Stonecat, and then Arkansas Darter. The probabilities of Flathead Chub successfully ascending a 6.1-m rock ramp fishway at slopes of 2, 4, and 6% were 1.0. Probability of Flathead Chub passage success was very high (0.96) for a 4.06-m, 8% slope fishway. Flathead Chub were unable to ascend 4.06-m of a 10% slope fishway. Stonecats had a passage probability of 1.0 for a 6.1-m fishway at 2 and 4% slope, and a passage probability of 0.83 for a 4.06-m, 6% slope fishway. No passage was predicted for 10% slope fishways greater than 4.06-m and 8% fishways greater than 6.1-m. Arkansas Darters never achieved a probability of 1.0 for ascending a 6.1-m fishway. However, their probability of partial passage success was moderate for a 2.03-m, 4% slope fishway with a probability of 0.43, and for a 4.06-m, 2% slope fishway with a probability of 0.54. Passage probabilities for Arkansas Darters were 0.00 for 10% slope 4.06-m, 8% slope 4.06-m, and 6% slope 6.10-m fishways. Based on the results of this study, it is clear that fishway designs should consider the passage requirements of the species with the lowest performance both in terms of fishway slope and fishway length. For example, a rock ramp fishway with a slope of 4% and a length of 2.03 m would be passable by some Arkansas Darters and all of the Stonecats and Flathead Chub in the size ranges tested. The results of this study provide valuable design criteria by identifying fishway slope and length combinations that allow passage of this representative suite of small-bodied Great Plains fishes.